HPV16/18 genotyping for the triage of HPV positive women in primary cervical cancer screening in Chile. Issue 1 (December 2015) - Lagos, Marcela; Van De Wyngard, Vanessa; Poggi, Helena; Cook, Paz; Viviani, Paola; Barriga, María; Pruyas, Martha; Ferreccio, Catterina
Abstract Background We previously conducted a population-based screening trial of high-risk human papillomavirus (hrHPV) testing and conventional cytology, demonstrating higher sensitivity (92.7 % vs 22.1 % for CIN2+) but lower positive predictive value (10.5 % vs 23.9 %) of hrHPV testing. Here we report the performance of HPV16/18 genotyping to triage the hrHPV positive participants. Methods Women aged 25 years and older received hrHPV (Hybrid Capture 2) and Papanicolaou testing; positives by either test underwent colposcopy and directed biopsy, as did a sample of double-negatives. hrHPV positive women were reflex-tested with HPV16/18 genotyping (Digene HPV Genotyping PS Test). Results Among the 8, 265 participants, 10.7 % were hrHPV positive, 1.7 % had ASCUS+ cytology, 1.2 % had CIN2+; 776 (88 %) hrHPV positive women had complete results, of whom 38.8 % were positive for HPV16 (24.0 %), HPV18 (9.7 %) or both (5.1 %). CIN2+ prevalence in HPV16/18 positive women (16.3 %, 95 % CI 12.3-20.9) was twice that of HPV16/18 negative women (8.0 %, 95 % CI 5.7-10.8). HPV16/18 genotyping identified 40.5 % of CIN2, 66.7 % of CIN3 and 75.0 % of cancers. Compared to hrHPV screening alone, HPV16/18 triage significantly reduced the referral rate (10.7 % vs 3.7 %) and the number of colposcopies required to detect one CIN2+ (9 vs 6). When HPV16/18 negative women with baseline ASCUS+ cytology were also colposcopied, an additional 14 % of CIN2+ was identified; referral increased slightly to 4.2 %. Conclusions HPV16/18 triage effectively stratified hrHPV positive women by their risk of high-grade lesions. HPV16/18 positive women must be referred immediately; referral could be deferred in HPV16/18 negative women given the slower progression of non-HPV16/18 lesions, however, they will require active follow-up.